On שבית,שרב and שבות in Psalm 85 - Alfred, Loader James (Journal for semitics, 2010)
This article considers a case of the appeal to etymology and the allied logic in Erich Zenger's commentary on the Psalms, often regarded as a flagship of present-day Psalms exegesis. The derivation of the words שבית ,שרב and שבות in Psalm 85:2 and the use to which this is put to achieve semantic results is examined with a view to the claim that the genre and meaning of the whole psalm are determined by this question. Issues of Ketiv and Qere and the semantics of the association of the two words are discussed in the light of other instances where the expression occurs. In the context of the author's rhetoric and inconsistencies between two almost simultaneous commentaries on the Psalms the question is posed as to the reason for pressing an argument in this way. After briefly comparing a small-scale but innovative reading of the psalm, it is respectfully submitted that even commentaries in the process of being canonised show fluctuations in methodological soundness.